Quality of match for statistical matches used in the development of the Levy Institute Measure of Time and Consumption Poverty (LIMTCP) for Ethiopia and South Africa - Fernando Rios-Avila (Levy Economics Institute of Bard College, 2020)
This paper presents a description of the quality of match of the statistical matches used in the LIMTCP estimates prepared for Ethiopia and South Africa. For Ethiopia, the statistical match combines the Ethiopian Socio-economic Survey-Wave 3-2015/2016 (ESS) with the Ethiopian Time Use Survey (ETUS) 2013. For South Africa it combines the October Household Survey (OHS) 1998 with the time use data obtained from the SA-Time Use Survey (SATUS) 2000, and the South African Living Conditions Survey (SALCS) 2014/2015 with the SATUS 2010. In all cases, the alignment of the two datasets is examined, after which various aspects of the match quality are described. Despite the differences in the survey years, the quality of match for South Africa is high and the synthetic dataset appropriate for the time poverty analysis. For Ethiopia, due to data quality differences, we restrict the analysis to married couple households with an employed spouse and young children. Conditioning on the restriction and sample reweighting, the Ethiopian synthetic dataset seems appropriate for the time poverty analysis.
Keywords: C14; C40; D31; J22; 330; Statistical Matching; Time Use; Household Production; Poverty; LIMTCP; Ethiopia; South Africa